The issue of evaluating the personnel potential of industrial enterprises - Olena Tarasevych (Cхід, 2017)
The article notes that the activities of industrial enterprises in modern conditions should be based on a high level of human resources. The model of estimation of personnel potential of industrial enterprises as one of the most important factors of influence on economic and financial results of enterprise activity is offered. The conclusion is made on the necessity of attracting, in order to increase the level of personnel potential of enterprises, to the staff of graduates of higher educational institutions, able to give optimal solutions for innovation and investment development of Ukrainian enterprises.